The DNA Damage Response: A Common Pathway in the Regulation of NKG2D and DNAM-1 Ligand Expression in Normal, Infected, and Cancer Cells - Cerboni, Cristina; Fionda, Cinzia; Soriani, Alessandra; Zingoni, Alessandra; Doria, Margherita; Cippitelli, Marco; Santoni, Angela (Frontiers in Immunology, 2014)
NKG2D and DNAM-1 are two activating receptors, present on the surface of NK cells and other cells of the immune system. Their ligands – MICA, MICB, ULBP1-6 for NKG2D, PVR/CD155 and Nectin-2/CD112 for DNAM-1 - can be constitutively expressed at low levels in some normal cells, but they are more often defined as “stress-induced”, since different stimuli can positively regulate their expression. In this review, we describe the molecular mechanisms involved in the up-regulation of NKG2D and DNAM-1 ligands under different physiological and pathological “stress” conditions, including mitosis, viral infections, and cancer. We will focus on the DNA damage response, as recent advances in the field have uncovered its important role as a common signaling pathway in the regulation of both NKG2D and DNAM-1 ligand expression in response to very diverse conditions and stimuli.